Pengaruh Metode Eksperimen Sawi Putih Terhadap Kemampuan Berpikir Kritis Anak Usia Dini Di Taman Kanak-Kanak Pertiwi 1 Kantor Gubernur Padang - Febrianty, Annisa; Yaswinda, Yaswinda (Childhood Education : Jurnal Pendidikan Anak Usia Dini, 2025)
The critical thinking abilities of young children at Pertiwi 1 Padang Kindergarten have not developed optimally because the learning used does not fully provide opportunities for children to think actively. The aim of conducting this research was to see how much influence the use of the chicory experimental method had on the critical thinking skills of young children at the Pertiwi 1 Kindergarten, Padang Governor's Office. This research uses a quasi-experiment with a quantitative approach. The data collection technique is through tests by making assessment instruments with checklists. Next, data analysis techniques were carried out using 3 swimmer tests, namely normality, homogeneity and hypothesis tests. The population in each Class B1 and B4 was 16 children, the sampling technique was 11 children. The results of the hypothesis test show that the significance value using Levene's Test for Equality of Variances is 0.193 > 0.05, meaning that the variance of the N-gain data for the two classes is homogeneous. Sign value. (2-tailed) of 0.010 < 0.05, meaning that there is a difference between the mustard greens experimental method on the critical thinking abilities of young children at Pertiwi 1 Kindergarten, Padang Governor's Office. So it can be concluded that the chicory experimental method has an effect on the critical thinking abilities of young children. In this case, the results of research using the chicory experimental method on children's critical thinking abilities can involve children in observing, raising questions, knowing cause and effect, solving problems, and expressing their opinions.